Osteoporosis Preventive Practice Between Veteran and Nonveteran Older Adults: Findings From Patient-Reported Data. (November 2016) - Nahm, Eun-Shim; Charters, Kathleen; Yoo, Eunhae; Keldsen, Linda M.; Zhu, Shijun
Abstract : BACKGROUND: Veterans are prone to bone-related illnesses due to multiple risk factors such as prior injuries. The aim of this study was to compare trends in osteoporosis preventive practices between veteran and nonveteran older adults. METHODS: This was a secondary data analysis using selected baseline data and discussion postings from an online bone health trial including participants ( N = 866) recruited from My HealtheVet (MHV) and SeniorNet (SN). Data were analyzed using descriptive statistics, parametric statistics, and content analysis. FINDINGS: Overall, MHV participants were younger and included more men than SN participants. However, they reported higher rates of bone health issues, spent less time exercising, took fewer calcium and vitamin D supplements, and were less likely to discuss bone health with their care providers. More MHV participants discussed pain and disability as barriers to bone health behaviors and fear of deteriorating health as motivators. In addition, more MHV participants found that participating in the original study was helpful for changing health behaviors. CONCLUSION: Overall, the findings suggest a disparity in bone health between veterans and nonveterans and a significant potential for using eHealth programs for veterans.